Syntheses of Chiral 2-Oxazolines from Isosorbide Epoxide Derivative - Mohammed Kadraoui; Stéphane Guillarme; Christine Saluzzo (Molbank)
Two chiral monooxazolines were synthesized from a secondary amino alcohol, as a key intermediate, isolated in four steps from an isosorbide-derived epoxide. The 2-oxazolines were then obtained through a reaction between this aminoalcohol and an imidate. The new compounds were fully characterized by FTIR, 1H and 13C NMR, and HRMS analyses.